2017
DOI: 10.1089/ten.tea.2016.0319
|View full text |Cite
|
Sign up to set email alerts
|

Braided and Stacked Electrospun Nanofibrous Scaffolds for Tendon and Ligament Tissue Engineering

Abstract: Tendon and ligament injuries are a persistent orthopedic challenge given their poor innate healing capacity. Nonwoven electrospun nanofibrous scaffolds composed of polyesters have been used to mimic the mechanics and topographical cues of native tendons and ligaments. However, nonwoven nanofibers have several limitations that prevent broader clinical application, including poor cell infiltration, as well as tensile and suture-retention strengths that are inferior to native tissues. In this study, multilayered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 62 publications
0
92
0
Order By: Relevance
“…Adequate mechanical properties are required for engineered tendon scaffolds, as tendons are subjected to dynamic mechanical forces in vivo [32]. Different human ligaments and tendons possess ultimate tensile strengths ranging from several to several hundred MPa and ultimate strain ranging 10 % to 50 %, depending on age, anatomy and measurement method [6365].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate mechanical properties are required for engineered tendon scaffolds, as tendons are subjected to dynamic mechanical forces in vivo [32]. Different human ligaments and tendons possess ultimate tensile strengths ranging from several to several hundred MPa and ultimate strain ranging 10 % to 50 %, depending on age, anatomy and measurement method [6365].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we fabricated PLLA fibrous meshes with controlled fiber diameter, orientation, and thickness by the adjustment of the appropriate spinning parameters. PLLA was chosen as the biomaterial for the tendon regeneration application because it is a fully biocompatible, biodegradable, synthetic material which can undergo remodeling and ultimately be replaced by regenerated tissue in vivo [43, 44]. In addition, PLLA is thermoplastics and it can be heated to its melting point, cooled, and reheated again without significant degradation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Two popular techniques are utilizing braided or twisted strands of material to increase stiffness and tensile strength, however encouraging cell infiltration can be challenging 13,[39][40][41][42] . A recent study comparing braided electrospun PCL sheets to stacked electrospun PCL sheets showed that the braided scaffolds possessed improved tensile strength which better mimicked the native ACL, however cell infiltration and proliferation was superior in stacked constructs 43 .…”
Section: Discussionmentioning
confidence: 99%